Analisis kesejahteraan petani padi di Kecamatan Air Hangat Timur Kabupaten Kerinci - Nanda Pratama; Zulfanetti Zulfanetti; Etik Umiyati (Jurnal Paradigma Ekonomika, 2021)
This research was conducted at Kerinci Regency, Air Hangat Timur sub-district, the largest rice harvesting area in Jambi Province. In this Air Hangat Timur sub-district area, the communities still use rice fields to cultivate rice as the primary commodity. This study aimed to determine rice farmers' welfare level in the Air Hangat Timur sub-district and determine the factors that affect the welfare of rice farmers based on predetermined indicators. This study used a quantitative descriptive analysis method, with the total sample used being 98 farmers from the entire population consisted 3531 rice farmers in Air Hangat Timur sub-district. Analyzing and testing the data, the researcher first carried out the classical assumption test using SPSS by obtaining the results of an Adjusted R square value of 0.848. It can be concluded that the independent variable used can explain 84.8% of the dependent variable. The remaining 15.2% is outside the variable in use. The majority of rice farmers in the Air Warm Timur Subdistrict are not poor. This can be seen from the per capita income level of Rp. 5,053,227 per year, while 9% of farmer families are classified as inferior if added up separately. According to the criteria of the Directorate of Land Use Rights, the remaining farmers in Air Warm Timur District are not in poor condition.